Twinning “Practices of Change” With “Theory of Change”: Room for Emerg ence in Advocacy Evaluation - Arensman, Bodille; Waegeningh, Cornelie; Wessel, Margit (American Journal of Evaluation, 2018)
Theory of change (ToC) is currently the approach for the evaluation an d planning of international development programs. This approach is con sidered especially suitable for complex interventions. We question thi s assumption and argue that ToC’s focus on cause–effect logic and inte nded outcomes does not do justice to the recursive nature of complex i nterventions such as advocacy. Supported by our work as evaluators, an d specifically our case study of an advocacy program on child rights, we illustrate how advocacy evolves through recursive interactions, wit h outcomes that are emergent rather than predictable. We propose putti ng “practices of change” at the center by emphasizing human interactio ns, using the analytical lenses of strategies as practice and recursiv eness. This provides room for emergent outcomes and implies a differen t use of ToC. In this article, we make a clear distinction between the oretical reality models and the real world of practices.